2015
DOI: 10.5109/1543403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Neuro–Fuzzy Inference System for Drought Forecasting in the Cai River Basin in Vietnam

Abstract: In order to achieve effective agricultural production, the impact of drought must be mitigated. An important requirement for mitigating the impact of drought is an effective method of forecasting future drought events. This paper presents the correlations between sea surface temperature anomalies (SSTA) and both the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI) at four areas monitoring El Nino-Southern Oscillation (ENSO) activities at the Cai River ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Shirmohammadi et al 2013 compared artificial neural networks, ANFIS, and support vector machines. Nguyen et al (2015) used SPI values for monitoring and forecasted using Fuzzy logic and ANFIS. and reported that the latter shows the best model even for the long and short-term time scales.…”
Section: Many Researchers Have Compared Standardizedmentioning
confidence: 99%
“…Shirmohammadi et al 2013 compared artificial neural networks, ANFIS, and support vector machines. Nguyen et al (2015) used SPI values for monitoring and forecasted using Fuzzy logic and ANFIS. and reported that the latter shows the best model even for the long and short-term time scales.…”
Section: Many Researchers Have Compared Standardizedmentioning
confidence: 99%
“…Shirmohammadi et al (2013) examined support vector machines, artificial neural networks, and ANFIS. Nguyen et al (2015) showed that ANFIS exhibits the best model even for the long and short term time scale and that SPI values were utilised for monitoring and forecasting. The primary goal of this study is to evaluate the drought in Tamilnadu's Coimbatore area using the SPI value.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, SPI is a non-linear method based on the drought prediction by conventional statistical methods with great uncertainty. Recently, the implementation of machine learning (ML) algorithms in SPI estimation and modeling such as support vector regression (SVR) (Belayneh et al, 2014;Borji et al, 2016), extreme learning machine (ELM) (M. Liu et al, 2021;Park et al, 2016), linear genetic programming (LGP) (Mehr et al, 2014), adaptive regression spline (MARS) (Deo et al, 2017), extremely randomized tree (ERT) , adaptive neuro-fuzzy inference system (ANFIS) (Gocić et al, 2015;Nguyen et al, 2015), artificial neural network (ANN) (Banadkooki et al, 2021;Deo and Şahin, 2015), M5 Tree (M5T) (Yaseen et al, 2021), and random forest (RF) (Danandeh Mehr et al, 2020; have presented huge potentials with promising results in estimating and modeling drought compared to conventional methods.…”
Section: Introductionmentioning
confidence: 99%